Lithium supplement material and preparation method thereof, positive electrode material and secondary battery
By using a combination of organic lithium salt and porous conductive substrate, the existing lithium supplement materials have solved the problems of poor air stability, large deliquency gas production and product residues, achieving efficient lithium-ion lithium supplementation effect and improving battery performance.
Patent Information
- Application Number
- CN202510069410.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-03-07
AI Technical Summary
The existing lithium supplement materials have problems such as poor air stability, large gas production of deliquency and residual deliquency products in the positive electrode sheet, which affects battery performance.
Lithium supplementary materials including organolithium salt Lix1Hx2CySz, including 6>x1>0, 5>x2≥0, y≥1, z≥1, combined with porous conductive substrates, were prepared by electrochemical or heat treatment synthesis methods.
The high air stability of lithium supplement materials, no deliquency production and no residue problems are achieved, and the energy density and charge and discharge efficiency of the battery are improved.
Smart Images

Figure CN119581566A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary batteries, and in particular to a lithium supplement material and a preparation method thereof, a positive electrode material and a secondary battery. Background Art
[0002] Lithium-ion batteries have the advantages of high operating voltage and energy density, relatively small self-discharge level, ultra-long cycle life, no memory effect, no pollution by heavy metal elements such as lead and cadmium, etc., and are widely used in many aspects such as electric vehicles, power tools, mobile electronic consumer products and energy storage. However, during the first charge and discharge process of lithium-ion batteries, a large amount of solid electrolyte interface film will be produced on the surface of the negative electrode of the battery, consuming the limited lithium ions and electrolyte in the battery, causing irreversible capacity loss, reducing the energy density of lithium-ion secondary batteries and reducing the charge and discharge efficiency of electrode materials, limiting the application of lithium-ion batteries.
[0003] Positive electrode lithium supplement materials can supplement the irreversible capacity loss caused by the formation of solid electrolyte interface film during the first charging process of lithium-ion batteries. It is one of the key technologies to improve the performance of lithium-ion batteries and has a broad application market and development prospects. However, most of the high-capacity lithium supplement materials in the existing technology face some common problems: poor air stability, large amount of gas produced by delithiation, and the delithiation products will remain in the positive electrode plate, which will have a certain negative impact on the plate and the battery. Therefore, how to provide a lithium supplement material with good air stability, no gas production and no residue has become the key. Summary of the invention
[0004] The purpose of the present invention is to provide a lithium supplement material and a preparation method thereof, a positive electrode material and a secondary battery, so as to solve the problems of poor air stability, gas generation and high residue of the existing lithium supplement material.
[0005] To achieve the purpose of the present invention, the present invention provides the following technical solutions:
[0006] In a first aspect, the present invention provides a lithium supplement material, wherein the lithium supplement material comprises an organic lithium salt, wherein the chemical formula of the organic lithium salt comprises Li x1 H x2 C y S z , where 6>x1>0, 5≥x2≥0, y≥1, z≥1.
[0007] In one embodiment, the organic lithium salt comprises a cyclic organic lithium salt, wherein y≥3, z=y, and the delithiation product of the cyclic organic lithium salt is C y S z , the C y S z Dissolved in electrolyte.
[0008] In one embodiment, the lithium supplement material further includes a porous conductive substrate, and the organic lithium salt is bound to the porous conductive substrate.
[0009] In one embodiment, the porous conductive substrate is a porous structure having holes and / or pores, and at least a portion of the organic lithium salt is confined and grown in the holes or pores.
[0010] In one embodiment, the particle size of the organic lithium salt is 3 nm to 100 nm.
[0011] In one embodiment, the mass fraction of the organic lithium salt in the lithium supplement material is 60% to 90%.
[0012] In one embodiment, the water absorption rate of the organic lithium salt in an environment with a temperature of 25° C. and a humidity of 30% is less than 3 ppm / s.
[0013] In one embodiment, the porosity of the porous conductive substrate is 50% to 95%.
[0014] In one embodiment, the pore size of the porous conductive substrate is 5 nm to 250 nm.
[0015] In one embodiment, the porous conductive substrate includes mesopores and macropores, the volume proportion of the mesopores is 20% to 50%, and the volume proportion of the macropores is 50% to 70%.
[0016] In one embodiment, the electronic conductivity of the porous conductive substrate is 1×10 3 S / m~1×10 7 S / m.
[0017] In one embodiment, the porous conductive substrate includes one or more of ordered mesoporous carbon, Ketjen black, carbon black, disordered porous carbon, porous graphene, carbon nanotubes, and carbon fibers.
[0018] In a second aspect, the present invention provides a method for preparing a lithium supplement material, comprising: combining a carbon-sulfur organic substance and a lithium source to obtain a precursor material; subjecting the precursor material to an electrochemical treatment or a heat treatment so that the carbon-sulfur organic substance and the lithium source react to obtain an organic lithium salt; the chemical formula of the organic lithium salt includes Li x1 H x2 C y S z , where 6>x1>0, 5≥x2≥0, y≥1, z≥1.
[0019] In a third aspect, the present invention provides a positive electrode material, which includes an active material and the lithium-supplementing material as described in the first aspect, or a lithium-supplementing material obtained by the preparation method of the lithium-supplementing material as described in the second aspect.
[0020] In a fourth aspect, the present invention provides a secondary battery comprising a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises the positive electrode material as described in the third aspect.
[0021] In one embodiment, the positive electrode includes a positive electrode plate, the positive electrode plate includes a current collector and a positive electrode material layer disposed on the current collector, the positive electrode material layer includes the positive electrode material, and the lithium-replenishing material content on the side of the positive electrode material layer close to the current collector is greater than the lithium-replenishing material content on the side of the positive electrode material layer away from the current collector.
[0022] In one embodiment, the positive electrode material layer includes a first layer and a second layer connected along the thickness direction, wherein the first layer is connected to the current collector, the mass fraction of the lithium-replenishing material in the first layer is 60% to 90% of the lithium-replenishing material in the positive electrode material layer, and the mass fraction of the lithium-replenishing material in the second layer is 10% to 40% of the lithium-replenishing material in the positive electrode material layer.
[0023] The lithium supplement material provided by the present invention includes an organic lithium salt, and the organic lithium salt is mainly composed of carbon atoms, sulfur atoms, and lithium atoms. The organic lithium salt not only has a high lithium supplement capacity (lithium supplement is greater than 300mAh / g), but also has a lower delithiation potential (1.3V~4V) than the existing lithium supplement materials; and the product after the organic lithium salt is delithiated is an organic molecule that is easily soluble in the electrolyte. The organic lithium salt will not generate gas after delithiation, and will not have a negative impact on the battery. The corresponding high-temperature storage process will not generate gas; in addition, the lithium supplement material provided by the present invention also has good air stability. At room temperature (25°C, humidity 30%), the water absorption rate of the lithium supplement material is below 3ppm / s. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1 is a schematic cross-sectional view of a lithium supplement material according to an embodiment;
[0026] Figure 2 is a flow chart of a method for preparing a lithium supplement material according to an embodiment;
[0027] Figure 3 is a schematic cross-sectional view of a positive electrode sheet according to an embodiment;
[0028] Figure 4 The present invention is a flow chart of a method for preparing a positive electrode sheet according to an embodiment;
[0029] Figure 5 The lithium supplement material Li in Example 1 6 C 6 S 6 EDS detection electron microscope image. DETAILED DESCRIPTION
[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used in the present invention includes any and all combinations of one or more of the related listed items.
[0032] It should be noted that the "range" disclosed in the present invention is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of a particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a specific parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present invention, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, wherein a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0033] All steps of the present invention may be performed sequentially or randomly, preferably sequentially. For example, a method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, a method may also include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b, etc.
[0034] Some embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.
[0035] The present invention provides a lithium supplement material 10, please refer to Figure 1 .
[0036] In one embodiment, the lithium supplement material 10 includes an organic lithium salt 11, and the chemical formula of the organic lithium salt 11 includes Li x1 H x2 C y S z , wherein 6>x1>0, 5≥x2≥0, y≥1, z≥1. Specifically, the organic lithium salt 11 refers to an organic compound containing lithium element, usually composed of lithium ions and organic anions. This structure enables the organic lithium salt 11 to have good solubility and electrochemical stability in the electrolyte. In the present invention, the organic lithium salt 11 is mainly composed of carbon atoms, sulfur atoms, and lithium atoms, and the organic lithium salt 11 may include hydrogen atoms or not.
[0037] The lithium replenishing material 10 provided by the present invention includes an organic lithium salt 11, and the organic lithium salt 11 is mainly composed of carbon atoms, sulfur atoms, and lithium atoms. The organic lithium salt 11 not only has a high lithium replenishing capacity (lithium replenishment is greater than 300mAh / g), but also has a lower delithiation potential (1.3V~4V) than the existing lithium replenishing material 10; and the product after the organic lithium salt 11 is delithiation is an organic molecule that is easily soluble in the electrolyte. The organic lithium salt 11 will not generate gas after delithiation, and will not have a negative impact on the battery. No gas will be generated during the corresponding high-temperature storage process; in addition, the lithium replenishing material 10 provided by the present invention also has good air stability. At room temperature (25°C, humidity 30%), the water absorption rate of the lithium replenishing material 10 is below 3ppm / s.
[0038] It should be noted that the organic lithium salt 11 provided by the present invention is different from the lithium sulfide (Li 2 S) or lithium polysulfide (Li n S m) and other inorganic lithium salts. Lithium sulfide (or lithium polysulfide) is an inorganic substance, and lithium sulfide does not include carbon atoms; while the organic lithium salt 11 including the above chemical formula is mainly composed of carbon atoms, and the carbon atoms can form a chain or ring structure, these structures can be open-chain or closed, lithium atoms and sulfur atoms are connected to the carbon chain, the open-chain structure is a chain organic lithium salt, and the closed structure is a ring organic lithium salt. Based on the difference in the precursors of the organic lithium salt 11, the corresponding chain organic lithium salt or ring organic lithium salt can be prepared by a chain precursor or a ring precursor. Therefore, due to the difference in structure between the chain and ring, the two will also have obvious differences in physical and chemical properties.
[0039] In addition, the organic lithium salt 11 provided by the present invention should also be distinguished from other lithium supplements in the prior art (such as lithium carbonate, lithium cobalt oxide, etc.). After the lithium supplements in the prior art are delithiated, the delithiation residues will remain in the battery in a solid form, thereby affecting the battery. The organic lithium salt 11 provided by the present invention will form an organic molecular product soluble in the electrolyte after delithiation. The organic molecular product is similar to the electrolyte and will not affect the battery or generate gas.
[0040] Furthermore, the organic lithium salt 11 (Li x1 H x2 C y S z ) is also different from the organic lithium supplements in the prior art (such as Li 2 CO 3 , Li 2 C 2 O 4 , Li x3 C 6 O 6 The specific differences include the following points: 1) The chemical element composition is different. The organic lithium salt 11 contains sulfur and no oxygen; 2) The preparation method is different. The organic lithium salt 11 is obtained by chemically reacting sulfur-containing organic matter (such as benzene hexathiol) with a lithium source, and may not contain hydrogen atoms when fully lithiated. The organic lithium salt 11 may be cyclic or chain-shaped, including -CS-SH groups (similar to S completely replacing the oxygen in the carboxyl group), and Li x3 C 6 O 6 Then it is C 6 O 6(Cyclohexanone) is prepared by electrochemical reaction to embed lithium; 3) The mechanism of action is different. The organic lithium salt 11 contains more types. When it does not contain hydrogen atoms, the bond energy of the carbon-sulfur bond in the organic lithium salt 11 is weaker, and the S element contains more electrons, which is beneficial to weaken the adjacent S-Li bond energy, so that lithium ions are more easily released from the material, thereby reducing the delithiation platform; 4) The impact on the battery is different. The sulfur element in the organic lithium salt 11 is closer to the electrolyte. Whether it is a chain or ring organic lithium salt 11, it can effectively improve the formation of SEI.
[0041] In one embodiment, the organic lithium salt 11 comprises a cyclic organic lithium salt, wherein y≥3, z=y, and the delithiation product of the cyclic organic lithium salt is C y S z , C y S z Specifically, the organic lithium salt 11 may be a cyclic organic lithium salt, that is, the carbon atoms may form a head-to-tail connected cyclic structure, and the lithium atoms and sulfur atoms are both connected to the carbon atoms. In a specific embodiment, the chemical formula of the organic lithium salt 11 may include Li x1 H x2 C 3 S 3 , Li x1 H x2 C 4 S 4 , Li x1 H x2 C 5 S 5 , Li x1 H x2 C 6 S 6 , Li x1 H x2 C 7 S 7 One or more of the above.
[0042] In the present invention, by providing a cyclic organic lithium salt 11, the solubility of the lithium supplement material 10 after delithiation in the electrolyte can be improved. Because the electrolyte components include carbonates or ethers, the cyclic organic lithium salt 11 after delithiation is also cyclic, which can be easily dissolved in the above electrolyte components without generating gas. At the same time, the above cyclic organic lithium salt 11 also has a higher lithium supplement capacity, such as Li 5 C 5 S 5 , Li 6 C 6 S 6 The lithium replenishment capacity can reach more than 300mAh / g. It can completely de-lithiate at a voltage cutoff of 4V. The de-lithiate product is C 6 S6 (cyclohexane hexathione) or C 5 S 5 (Cyclopentanepentathione).
[0043] In one embodiment, the organic lithium salt 11 is a chain organic lithium salt, and the ratio of z to y is not specifically limited. The carbon atoms may form a chain structure connected in sequence, and the lithium atoms and sulfur atoms are both connected to the carbon atoms.
[0044] In one embodiment, the chemical formula of the organic lithium salt 11 includes Li x1 C y S z , wherein 6>x1>0; or the chemical formula of the organic lithium salt 11 includes Li x1 H x2 C y S z , wherein 6>x1>0, 5≥x2≥0. It should be noted that, in a specific embodiment, the organic lithium salt 11 may not include hydrogen atoms, and the lithium content in the organic lithium salt 11 is higher when hydrogen atoms are not included. Of course, in the case of containing hydrogen atoms, the presence of hydrogen atoms has a certain electron-donating effect, which can weaken the S-Li bond, thereby reducing the delithiation potential to a certain extent; this type of material is more suitable for ternary materials and some solid-state battery systems that do not require so much lithium replenishment capacity but are more demanding on the voltage platform.
[0045] In one implementation, please refer to Figure 1 The lithium supplement material 10 further includes a porous conductive substrate 12, and the organic lithium salt 11 is combined on the porous conductive substrate 12. The present invention improves the overall electronic conductivity of the lithium supplement material 10 by compounding the organic lithium salt 11 with the porous conductive substrate 12 and utilizing the high conductivity of the porous conductive substrate 12, thereby improving the rate performance of the lithium supplement material 10.
[0046] In one embodiment, the porous conductive substrate 12 includes one or more of ordered mesoporous carbon (CMK-3), Ketjen black (KB), carbon black (SP), disordered porous carbon with a large specific surface area (SPC), porous graphene, carbon nanotubes (CNT), and carbon fibers (CNF).
[0047] In one embodiment, the organic lithium salt 11 may be combined with the outside or inside of the porous conductive substrate 12; alternatively, the organic lithium salt 11 may be combined with the inside of the porous conductive substrate 12, or the organic lithium salt 11 may be coated on the outside of the porous conductive substrate 12.
[0048] In one implementation, please refer to Figure 1The porous conductive substrate 12 is a porous structure having holes or pores 13, and at least part of the organic lithium salt 11 is confined and grown in the holes or pores 13. The present invention confines the organic lithium salt 11 through the holes or pores 13 on the porous conductive substrate 12, which can limit the particle size of the organic lithium salt 11, thereby promoting the electronic contact between the organic lithium salt 11 and the porous conductive substrate 12.
[0049] In one embodiment, the particle size of the organic lithium salt 11 is 3nm to 100nm. Optionally, the particle size of the organic lithium salt 11 can be 3nm, 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm. Meeting the particle size of the organic lithium salt 11 within the above range, on the one hand, the capacity of the organic lithium salt 11 can be fully released, and on the other hand, the organic lithium salt 11 can be accommodated in the pores 13 of the porous conductive substrate 12. When the particle size of the organic lithium salt 11 is too small, the difficulty of preparing the organic lithium salt 11 increases, and it is easy to agglomerate. When the particle size of the organic lithium salt 11 is too large, the capacity of the organic lithium salt 11 cannot be fully released, and the organic lithium salt 11 is difficult to accommodate in the pores, but is combined with the outside of the porous conductive substrate 12.
[0050] In one embodiment, the mass fraction of the organic lithium salt 11 in the lithium replenishing material 10 is 60% to 90%. Optionally, the mass fraction of the organic lithium salt 11 in the lithium replenishing material 10 is 60%, 65%, 70%, 75%, 80%, 85%, 90%. When the mass fraction of the organic lithium salt 11 in the lithium replenishing material 10 is within the above range, the capacity of the lithium replenishing material 10 and the conductivity of the lithium replenishing material 10 can be ensured. When the proportion of the organic lithium salt 11 is too small, the lithium replenishing capacity of the lithium replenishing material 10 is reduced. When the proportion of the organic lithium salt 11 is too large, the conductivity of the lithium replenishing material 10 decreases.
[0051] In one embodiment, the water absorption rate of the organic lithium salt 11 in an environment with a temperature of 25° C. and a humidity of 30% is less than 3 ppm / s. Optionally, the water absorption rate of the organic lithium salt 11 may be 0.5 ppm / s, 1 ppm / s, 1.5 ppm / s, 2 ppm / s, 2.5 ppm / s, or 3 ppm / s.
[0052] In one embodiment, the porosity 13 of the porous conductive substrate 12 is 50% to 95%. When the porosity 13 of the porous conductive substrate 12 is within the above range, it can be ensured that the porous conductive substrate 12 has sufficient space to load the organic lithium salt 11, and the structural stability of the porous conductive substrate 12 can also be ensured. When the porosity 13 of the porous conductive substrate 12 is too small, the organic lithium salt 11 is mostly loaded on the outside of the porous conductive substrate 12, resulting in a decrease in the conductivity of the lithium supplement material 10. When the porosity 13 of the porous conductive substrate 12 is too large, the structural stability of the porous conductive substrate 12 deteriorates.
[0053] In one embodiment, the pore size of the porous conductive substrate 12 is 5nm to 250nm. Optionally, the pore size of the porous conductive substrate 12 can be 5nm, 10nm, 20nm, 50nm, 100nm, 150nm, 200nm, 250nm. When the pore size of the porous conductive substrate 12 is within the above range, it can be ensured that the porous conductive substrate 12 achieves a confinement effect on the organic lithium salt 11 through the pores 13. When the pore size of the porous conductive substrate 12 is too small, the organic lithium salt 11 is difficult to be confined to the pores 13 of the porous conductive substrate 12. When the pore size of the porous conductive substrate 12 is too large, the particles of the organic lithium salt 11 are also correspondingly too large.
[0054] In one embodiment, the porous conductive substrate 12 includes mesopores and macropores, the volume of the mesopores accounts for 20% to 50%, and the volume of the macropores accounts for 50% to 70%. Specifically, the volume of the mesopores and macropores refers to the size of the space occupied by the holes on the porous conductive substrate 12, that is, the percentage of the volume of the holes in the overall volume of the porous conductive substrate 12. Optionally, the volume of the mesopores can account for 20%, 30%, 40%, 50%, and the volume of the macropores can account for 50%, 60%, 70%. When the volume of the mesopores and macropores is within the above range, the confinement effect of the pores 13 on the organic lithium salt 11 can be ensured.
[0055] In one embodiment, the electronic conductivity of the porous conductive substrate 12 is 1×10 3 S / m~1×10 7 S / m. Optionally, the electronic conductivity of the porous conductive substrate 12 may be 1×10 3 S / m, 1×10 4 S / m, 1×10 5 S / m, 1×10 6 S / m, 1×10 7 S / m.
[0056] The present invention provides a method for preparing a lithium supplement material. Figure 2 .
[0057] In one embodiment, the preparation method of the lithium supplement material specifically comprises the following steps:
[0058] Step S10, combining carbon-sulfur organic matter and a lithium source to obtain a precursor material.
[0059] Step S20, electrochemically or thermally treating the precursor material to react the carbon-sulfur organic matter with the lithium source to obtain an organic lithium salt.
[0060] In one embodiment, in step S10, the carbon-sulfur organic matter is a precursor of the organic lithium salt, and the carbon-sulfur organic matter may include only organic matter (chain or ring) of carbon atoms and sulfur atoms, and the carbon-sulfur organic matter may also include organic matter (chain or ring) of carbon atoms, sulfur atoms and hydrogen atoms. In a specific embodiment, the carbon-sulfur organic matter may include but is not limited to cyclohexanethione (C 6 S 6 ), cyclopentanepentathione (C 5 S 5 ), benzene hexathiophenol (C 6 S 6 H 6 ) etc.
[0061] In one embodiment, the lithium source may be elemental lithium. Of course, it is necessary to distinguish the lithium source in the prior art from the lithium source provided by the present invention, which is a lithium source that does not contain oxygen atoms. Because most of the lithium supplements in the prior art are oxygen-containing lithium compounds (such as lithium-rich lithium cobalt oxide, lithium carbonate, etc.), most of their lithium sources are lithium oxide, lithium hydroxide, lithium carbonate, etc. However, in order to avoid the introduction of oxygen atoms in the present invention, elemental lithium is directly used as the lithium source, which can also increase the content of lithium atoms embedded in carbon and sulfur organic matter.
[0062] In one embodiment, in step S20, based on the differences between carbon-sulfur organic matter, the preparation method of the lithium supplement material provided by the present invention specifically includes two methods: electrochemical synthesis method and thermal treatment synthesis method. Among them, the electrochemical synthesis method mainly uses the charging and discharging method to embed lithium ions into carbon-sulfur organic matter to obtain a product; the thermal treatment synthesis method mainly uses the calcination method to react the two to obtain a product.
[0063] In one embodiment, the lithium supplement material is prepared by electrochemical synthesis, which specifically includes the following steps:
[0064] Step A10, mixing carbon-sulfur organic matter and a carbon source as a positive electrode, using a lithium sheet as a negative electrode, and assembling the positive electrode, the negative electrode and an electrolyte together into a battery.
[0065] Step A20, performing electrochemical treatment on the battery in a preset discharge environment, disassembling the battery after the electrochemical treatment to obtain a positive electrode, wherein the positive electrode includes an organic lithium salt.
[0066] In one embodiment, in step A10, the carbon source includes one or more of ordered mesoporous carbon (CMK-3), Ketjen black (KB), carbon black (SP), disordered porous carbon with large specific surface area (SPC), porous graphene, carbon nanotubes (CNT), and carbon fibers (CNF). The electrolyte may be an electrolyte, and in the case of including an electrolyte, the battery also includes a separator. In this embodiment, the battery is the precursor material in step S10 of the above embodiment.
[0067] In one embodiment, in step A10, the carbon-sulfur organic matter and the carbon source are mixed in a manner including: mixing the carbon-sulfur organic matter and the carbon source, and heat treating the obtained mixture so that the carbon-sulfur organic matter melts and diffuses into the pores of the carbon source.
[0068] In one embodiment, in step A20, the preset discharge environment may be: discharging the battery to 1.2 V. Of course, other discharge environments may also be used, and are not specifically limited. It should be explained that the main purpose of the electrochemical treatment is to release the lithium ions in the negative electrode to the positive electrode, and the lithium ions are embedded in the carbon-sulfur organic matter.
[0069] The lithium supplement material prepared by the electrochemical synthesis method provided by the present invention first melts carbon-sulfur organic matter and composites it with a carbon source, uses the pores of the carbon source to physically limit the particle size of the reactants, and adjusts the discharge current density of the electrochemical reaction to promote the full progress of the reaction, and limits the growth of organic lithium salt particles, thereby obtaining a composite of an organic lithium salt and a porous conductive substrate. This structural design promotes the electronic contact between the organic lithium salt and the conductive carrier, improves the overall electronic conductivity of the lithium supplement material, and thereby improves the rate performance of the organic lithium salt.
[0070] In one embodiment, the lithium supplement material prepared by the heat treatment synthesis method specifically includes the following steps:
[0071] Step B10, mixing the carbon-sulfur organic matter and the carbon source in proportion to obtain a precursor material.
[0072] Step B20, heat-treating the precursor material to allow the carbon-sulfur organic matter to react with the lithium source to obtain an organic lithium salt.
[0073] In one embodiment, in step B10, the carbon-sulfur organic matter and the carbon source are mixed in a molar ratio, and the molar ratio conforms to the chemical formula of the organic lithium salt provided in the above embodiment.
[0074] The invention provides a positive electrode material.
[0075] In one embodiment, the positive electrode material includes a positive electrode active material and a lithium supplement material. The lithium supplement material is the lithium supplement material provided in the above embodiment. Optionally, the positive electrode active material can be a phosphate positive electrode active material or a ternary positive electrode active material. In a specific embodiment, the positive electrode active material includes one or more of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium vanadium phosphate, lithium vanadium oxyphosphate, lithium fluorinated vanadium phosphate, lithium titanate, lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide.
[0076] In one embodiment, the content of lithium-supplementing material in the positive electrode material can be controlled at 1% to 6% of the mass of the positive electrode active material. This ratio can just make up for the loss of active lithium in the battery during the first charging process. If the amount of lithium-supplementing material added to the positive electrode material is too low, the active lithium lost in the positive electrode active material cannot be fully replenished, which is not conducive to improving the energy density and capacity retention rate of the battery. If the amount of lithium-supplementing material added to the positive electrode active material is too high, the original reversible capacity will be occupied and the cost will be increased. In some specific embodiments, in the positive electrode material, the mass percentage of the lithium-supplementing material can be 1%, 2%, 4%, 6%, etc.
[0077] The present invention provides a secondary battery.
[0078] In one embodiment, the present invention further provides a secondary battery, the secondary battery comprising a negative electrode, a positive electrode and an electrolyte, wherein the positive electrode comprises the above-mentioned positive electrode material; the electrolyte may be an electrolyte solution, in which case the secondary battery further comprises a diaphragm disposed between the positive electrode plate and the negative electrode plate; or, the electrolyte may be a solid electrolyte solution, in which case the secondary battery does not have a diaphragm and is replaced by a solid electrolyte.
[0079] In one embodiment, the positive electrode includes a positive electrode plate, see Figure 3 The positive electrode plate includes a current collector 200 and a positive electrode material layer 100 arranged on the current collector 200, the positive electrode material layer 100 includes a positive electrode material, and the lithium-supplementing material content on the side of the positive electrode material layer 100 close to the current collector 200 is greater than the lithium-supplementing material content on the side of the positive electrode material layer 100 away from the current collector 200.
[0080] In the prior art, since it is more difficult for the electrolyte to penetrate into the inner layer of the positive electrode plate (the side close to the current collector 200), the present invention provides an optimized positive electrode plate as described above. By setting a higher content of lithium-supplementing material 10 on the side connected to the current collector 200, after the lithium-supplementing material 10 is delithiated and its product is dissolved in the electrolyte during the formation stage, some vacancies or pores are generated in the part of the positive electrode material layer 100 connected to the current collector 200, which is convenient for the electrolyte to fully penetrate and diffuse in the inner layer of the positive electrode plate in subsequent cycles, thereby reducing the distance of lithium ion migration, which is beneficial to improving the rate performance of the battery.
[0081] In one embodiment, the positive electrode material layer 100 includes components such as positive electrode active material, lithium supplement material 10, conductive agent, binder, etc. The present invention does not specifically limit these materials, and suitable materials can be selected according to actual application requirements. The current collector 200 includes but is not limited to any one of copper foil and aluminum foil. The conductive agent includes one or more of graphite, carbon black, acetylene black, graphene, carbon fiber, C60 and carbon nanotubes, and the content of the conductive agent in the positive electrode material layer 100 is 3wt% to 5wt%. The types of binders include one or more of polyvinylidene chloride, soluble polytetrafluoroethylene, styrene-butadiene rubber, hydroxypropyl methylcellulose, methylcellulose, carboxymethyl cellulose, polyvinyl alcohol, acrylonitrile copolymer, sodium alginate, chitosan and chitosan derivatives, and the content of the binder in the positive electrode material layer 100 is 2wt% to 4wt%.
[0082] In one embodiment, the mass proportion of the lithium supplement material 10 in the positive electrode material layer 100 is 0.5% to 6%. Optionally, the mass proportion of the lithium supplement material 10 in the positive electrode material layer 100 can be 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%. Among them, the lithium supplement material 10 is mainly distributed on the side close to the current collector 200 in the positive electrode material layer 100, so the content of the lithium supplement material 10 at the first side 100A is greater than the content of the lithium supplement material 10 at the second side 100B.
[0083] In one implementation, please refer to Figure 3 The positive electrode material layer 100 includes a first layer 101 and a second layer 102 connected along the thickness direction, wherein the first layer 101 is connected to the current collector 200, the first layer 101 includes a first surface 100A, and the second layer 102 includes a second surface 100B. The mass fraction of the lithium-replenishing material 10 in the first layer 101 accounts for 60% to 90% of the lithium-replenishing material 10 in the positive electrode material layer 100, and the mass fraction of the lithium-replenishing material 10 in the second layer 102 accounts for 10% to 40% of the lithium-replenishing material 10 in the positive electrode material layer 100.
[0084] Specifically, the positive electrode material layer 100 may include a first layer 101 and a second layer 102 which are stacked, wherein the second layer 102 is disposed above the first layer 101, and the lithium supplement material 10 is mainly distributed in the first layer 101, so the content of the lithium supplement material 10 in the first layer 101 is greater than the content of the lithium supplement material 10 in the second layer 102. It should be explained that in the actual positive electrode sheet, the stratification (first layer 101 and second layer 102) of the positive electrode material layer 100 does not need to be clearly seen; instead, in the process of preparing the positive electrode sheet, at least two positive electrode slurries may be provided, and the contents of the lithium supplement material 10 in the two positive electrode slurries are different, and the positive electrode material with a high content of the lithium supplement material 10 is used to first coat the first layer 101, and the positive electrode material with a low content of the lithium supplement material 10 is used to later coat the second layer 102.
[0085] Further, the mass fraction of the lithium supplement material 10 in the first layer 101 to the lithium supplement material 10 in the positive electrode material layer 100 is 60% to 90%, which means that the lithium supplement material 10 in the first layer 101 accounts for 60% to 90% of the lithium supplement material 10 (in the positive electrode material layer 100); the mass fraction of the lithium supplement material 10 in the second layer 102 to the lithium supplement material 10 in the positive electrode material layer 100 is 10% to 40%, which means that the lithium supplement material 10 in the second layer 102 accounts for 10% to 40% of the lithium supplement material 10 (in the positive electrode material layer 100). In a specific embodiment, the mass of the positive electrode material layer 100 is 100g, the mass fraction of the lithium supplement material 10 is 6% (6g), the content of the lithium supplement material 10 in the first layer 101 is 100g×6%×90%=5.4g, and the content of the lithium supplement material 10 in the second layer 102 is 100g×6%×10%=0.6g.
[0086] Optionally, the mass fraction of the lithium-supplementing material 10 in the first layer 101 to the lithium-supplementing material 10 in the positive electrode material layer 100 may be 60%, 65%, 70%, 75%, 80%, 85%, 90%. The mass fraction of the lithium-supplementing material 10 in the second layer 102 to the lithium-supplementing material 10 in the positive electrode material layer 100 may be 10%, 15%, 20%, 25%, 30%, 35%, 40%.
[0087] In one implementation, please refer to Figure 3 , the positive electrode material layer 100 further includes a third layer 103, and the third layer 103 is disposed on the side of the second layer 102 facing away from the first layer 101, and the mass fraction of the lithium supplement material 10 in the third layer 103 is 0% of the lithium supplement material 10 in the positive electrode material layer 100. Specifically, based on the above embodiment, in the process of preparing the positive electrode sheet, a positive electrode slurry can be provided, and the lithium supplement material 10 is not added to the positive electrode slurry, and the positive electrode material is used to prepare the third layer 103.
[0088] In one embodiment, the thickness of the first layer 101 is greater than or equal to the thickness of the second layer 102, and the thickness of the second layer 102 is greater than or equal to the thickness of the third layer 103; that is, the thickness of the positive electrode material layer 100 is D, the thickness of the first layer 101 is d1, the thickness of the second layer 102 is d2, and the thickness of the third layer 103 is d3, d1≥d2≥d3, d1+d2+d3=D. In a specific embodiment, d1=d2=d3.
[0089] In one embodiment, in the first layer 101 , the mass fraction of the positive electrode active material is 78.8% to 94.1%, the mass fraction of the lithium supplement material 10 is 0.9% to 16.2%, and the mass fraction of the binder and the conductive agent is 5%.
[0090] In one embodiment, in the second layer 102 , the mass fraction of the positive electrode active material is 90.5% to 94.85%, the mass fraction of the lithium supplement material 10 is 0.15% to 4.5%, and the mass fraction of the binder and the conductive agent is 5%.
[0091] In one embodiment, in the third layer 103 , the mass fraction of the positive electrode active material is 95%, and the mass fraction of the binder and the conductive agent is 5%.
[0092] In one embodiment, the number of positive electrode material layers 100 is a multi-layer coating structure, and the number of material layers in the positive electrode material layer 100 is greater than or equal to three.
[0093] The present invention provides a method for preparing a positive electrode plate, please refer to Figure 4 .
[0094] In one embodiment, the method for preparing the positive electrode sheet specifically comprises the following steps:
[0095] Step S100, adding the positive electrode active material, the lithium supplement material, the conductive agent and the binder into the organic solvent according to a first ratio, fully dispersing and stirring to obtain a first slurry.
[0096] Step S200, coating the first slurry on the current collector, and obtaining a current collector having a first layer after drying.
[0097] Step S300, adding the positive electrode active material, the lithium supplement material, the conductive agent and the binder into the organic solvent according to the second ratio, fully dispersing and stirring to obtain a second slurry.
[0098] Step S400, coating the second slurry on the first layer, and obtaining a current collector having a second layer after drying.
[0099] Step S500, adding the positive electrode active material, the conductive agent and the binder into the organic solvent according to a third ratio, fully dispersing and stirring to obtain a third slurry.
[0100] Step S600, coating the third slurry on the second layer, and obtaining a current collector having the third layer after drying.
[0101] The content of the lithium-replenishing material in the first ratio is greater than the content of the lithium-replenishing material in the second ratio.
[0102] The technical solution of the present invention is described in detail below through specific embodiments.
[0103] Example 1
[0104] This embodiment provides a lithium supplement material. The lithium supplement material includes a cyclic organic lithium salt (Li 6 C 6 S 6 ) and a porous conductive substrate (CMK-3), the porous conductive substrate is a porous structure with pores. The particle size of the organic lithium salt is 50nm, the mass fraction of the organic lithium salt in the lithium supplement material is 75%, the porosity of the porous conductive substrate is 80%, the pore size of the porous conductive substrate is 100nm, the volume proportion of mesopores on the porous conductive substrate is 30%, and the volume proportion of macropores is 60%.
[0105] The preparation method of the lithium supplement material comprises the following steps:
[0106] 1) 10g of C 6 S 6 8H 2 O was added into a 500 mL round-bottom flask, and the flask was placed in an oil bath and heated at 180 °C for 12 h. During the heating process, a vacuum treatment was performed to remove the crystal water to obtain C 6 S 6 (cyclohexanehexathione), and then crush it into powder.
[0107] 2) Place the commercially available CMK-3 in a tube furnace and introduce nitrogen, raise the temperature to 950°C at a rate of 5°C / min, and then introduce CO at a flow rate of 10 mL / min. 2 The material was kept warm for 1 hour for activation treatment, and then nitrogen was introduced to cool it down to room temperature naturally. After the activation treatment was completed, the material was placed in an Ar gas atmosphere at a temperature of 1500°C for 2 hours to reduce defects.
[0108] 3) C obtained in step 1) 6 S 6 The powder (6 g) was thoroughly mixed with the commercially available CMK-3 ordered mesoporous carbon (2 g) treated as above in a glove box, and then heated to 150° C. for 10 h. 6 S 6 The melt diffuses into the internal pores of CMK-3 and is physically confined to obtain C6 S 6 @CMK-3.
[0109] 4) C 6 S 6 @CMK-3 is pressed into a sheet as the positive electrode, and assembled into a button battery together with a lithium sheet (as the negative electrode), electrolyte, and separator, etc., and discharged to 1.2V. The above C 6 S 6 Completely converted to Li 6 C 6 S 6 , get Li 6 C 6 S 6 @CMK-3, disassemble the battery, clean the positive electrode with pure DMC solvent, and dry it in a glove box to obtain the lithium replenishing material.
[0110] Figure 5 Lithium supplement material Li 6 C 6 S 6 EDS (Energy Dispersive Spectrometer) detection electron microscope picture, Table 1 is the lithium supplement material Li 6 C 6 S 6 EDS test results. Among them, Figure 5 A) is the lithium supplement material Li 6 C 6 S 6 Scanning electron image, B) is the distribution of C (carbon element) in the corresponding image A), C) is the distribution of S (sulfur element) in the corresponding image A); combined with the mass ratio statistics of C and S in Table 1, it can be clearly seen that the lithium supplement material Li can be prepared by the above preparation method 6 C 6 S 6 .
[0111] Table 1 Lithium supplement materials Li 6 C 6 S 6 EDS test results
[0112] element Line Type Apparent concentration k ratio wt% wt% Sigma Standard sample label C K-line system 9.23 0.09231 39.59 0.54 C Vit S K-line system 24.41 0.08214 57.24 0.55 <![CDATA[FeS 2 ]]> Al K-line system 0.12 0.00084 0.30 0.08 <![CDATA[Al 2 THE 3 ]]> Co K-line system 0.93 0.00926 2.86 0.35 Co Total 100.00
[0113] Example 2
[0114] This embodiment provides a lithium supplement material. The difference between this lithium supplement material and the lithium supplement material provided in embodiment 1 is that the particle size of the organic lithium salt is 120 nm.
[0115] The difference between the preparation method of the lithium supplement material and the preparation method provided in Example 1 is that the insulation time at 150° C. in step 3) is adjusted to 6 hours.
[0116] Example 3
[0117] This embodiment provides a lithium supplement material. The difference between this lithium supplement material and the lithium supplement material provided in embodiment 1 is that the mass fraction of the organic lithium salt in the lithium supplement material is 50%.
[0118] The difference between the preparation method of the lithium supplement material and the preparation method provided in Example 1 is that in step 3), the mass of the commercially available CMK-3 ordered mesoporous carbon is adjusted to 6 g.
[0119] Example 4
[0120] This embodiment provides a lithium supplement material. The difference between this lithium supplement material and the lithium supplement material provided in embodiment 1 is that the mass fraction of the organic lithium salt in the lithium supplement material is 95%.
[0121] The difference between the preparation method of the lithium supplement material and the preparation method provided in Example 1 is that the mass of commercially available CMK-3 in step 3) is adjusted to 0.316 g.
[0122] Example 5
[0123] This embodiment provides a lithium supplement material. The difference between this lithium supplement material and the lithium supplement material provided in embodiment 1 is that the porosity of the porous conductive substrate is 49%.
[0124] The difference between the preparation method of the lithium supplement material and the preparation method provided in Example 1 is that the CMK-3 in step 2) is not subjected to CO 2 Activation treatment.
[0125] Example 6
[0126] This embodiment provides a lithium supplement material. The difference between this lithium supplement material and the lithium supplement material provided in embodiment 1 is that the porosity of the porous conductive substrate is 96%.
[0127] The preparation method of the lithium supplement material is different from the preparation method provided in Example 1 in that: in step 2), the CO of CMK-3 2 The activation temperature was adjusted to 1000°C.
[0128] Example 7
[0129] This embodiment provides a lithium supplement material. The difference between this lithium supplement material and the lithium supplement material provided in embodiment 1 is that the pore size of the porous conductive substrate is 4 nm.
[0130] The difference between the preparation method of the lithium supplement material and the preparation method provided in Example 1 is that the CMK-3 in step 2) is not subjected to CO 2 Activation treatment.
[0131] Example 8
[0132] This embodiment provides a lithium supplement material. The difference between this lithium supplement material and the lithium supplement material provided in embodiment 1 is that the pore size of the porous conductive substrate is 260 nm.
[0133] The preparation method of the lithium supplement material is different from the preparation method provided in Example 1 in that: CO 2 The activation treatment time was adjusted to 10 h.
[0134] Example 9
[0135] This embodiment provides a lithium supplement material. The difference between this lithium supplement material and the lithium supplement material provided in embodiment 1 is that the volume proportion of mesopores on the porous conductive substrate is 20%, and the volume proportion of macropores is 49%.
[0136] The difference between the preparation method of the lithium supplement material and the preparation method provided in Example 1 is that the time of argon treatment at 1500° C. in step 2) is adjusted to 8 hours.
[0137] Example 10
[0138] This embodiment provides a lithium supplement material. The difference between this lithium supplement material and the lithium supplement material provided in embodiment 1 is that the volume proportion of mesopores on the porous conductive substrate is 20%, and the volume proportion of macropores is 71%.
[0139] The difference between the preparation method of the lithium supplement material and the preparation method provided in Example 1 is that the 1500° C. argon treatment in step 2) is removed.
[0140] Embodiment 11
[0141] This embodiment provides a lithium supplement material. The difference between this lithium supplement material and the lithium supplement material provided in embodiment 1 is that the lithium supplement material includes a cyclic organic lithium salt (Li 5 C 5 S 5 ) and a porous conductive substrate (CMK-3).
[0142] The preparation method of the lithium supplement material is different from the preparation method provided in Example 1 in that: C 6 S 6 8H 2 O to C 5 S 5 8H 2 O, other things remain unchanged.
[0143] Example 12
[0144] This embodiment provides a lithium supplement material. The difference between this lithium supplement material and the lithium supplement material provided in Example 1 is that the lithium supplement material only includes a cyclic organic lithium salt containing a benzene ring (Li 6 C 6 S 6 ).
[0145] The preparation method of the lithium supplement material comprises the following steps:
[0146] 1) Benzene hexathiophenol (C 6 S 6 H 6 ) and lithium in a molar ratio of 1:6 are fully mixed, heated to 200°C, and kept warm for 6 hours to obtain Li 6 C 6 S 6 .
[0147] 2) The positive electrode active material, lithium supplement material, conductive agent and binder are dispersed and stirred together with NMP (N-methylpyrrolidone) according to the above-mentioned stoichiometric ratio to form a slurry, and then coated on aluminum foil and dried to obtain the first layer.
[0148] 3) The positive electrode active material, lithium supplement material, conductive agent and binder are dispersed and stirred together with NMP (N-methylpyrrolidone) according to the above-mentioned stoichiometric ratio to form a slurry, and then coated on aluminum foil and dried to obtain the second layer.
[0149] 4) The positive electrode active material, the conductive agent and the binder are dispersed and stirred together with NMP (N-methylpyrrolidone) according to the above-mentioned stoichiometric ratio to form a slurry, and then coated on an aluminum foil and dried to obtain the third layer.
[0150] Embodiment 13
[0151] This embodiment provides a lithium supplement material. The difference between this lithium supplement material and the lithium supplement material provided in Example 1 is that the lithium supplement material includes a chain organic lithium salt (LiSSC-CSSLi, i.e. Li 2 C 2 S 4 ) and a porous conductive substrate (CMK-3).
[0152] The preparation method of the lithium supplement material is as follows:
[0153] 1) Place the commercially available CMK-3 in a tube furnace and introduce nitrogen. Raise the temperature to 950°C at a rate of 5°C / min, and then introduce CO at a flow rate of 10 mL / min. 2 The material was kept warm for 1 hour for activation treatment, and then nitrogen was introduced to cool it down to room temperature naturally. After the activation treatment was completed, the material was placed in an Ar gas atmosphere at a temperature of 1500°C for 2 hours to reduce defects.
[0154] 2) HSSC-CSSH (6 g) was thoroughly mixed with the commercially available CMK-3 ordered mesoporous carbon (2 g) treated as above in a glove box, and then heated to 150°C for 10 h. HSSC-CSSH melted and diffused into the internal pores of CMK-3, and was physically confined to obtain HSSC-CSSH@CMK-3.
[0155] 3) The HSSC-CSSH@CMK-3 obtained in step 2) and the elemental lithium were mixed evenly in a molar ratio of 1:2 between HSSC-CSSH and the elemental lithium, and heated to 200°C for 6 hours to obtain Li 2 C 2 S 4 @CMK-3.
[0156] Embodiment 14
[0157] This embodiment provides a lithium supplement material. The difference between this lithium supplement material and the lithium supplement material provided in embodiment 1 is that the lithium supplement material includes a cyclic organic lithium salt (Li 5 HC 6 S 6 ) and a porous conductive substrate (CMK-3).
[0158] The preparation method of the lithium supplement material:
[0159] 1) Place the commercially available CMK-3 in a tube furnace and introduce nitrogen. Raise the temperature to 950°C at a rate of 5°C / min, and then introduce CO at a flow rate of 10 mL / min. 2 The material was kept warm for 1 hour for activation treatment, and then nitrogen was introduced to cool it down to room temperature naturally. After the activation treatment was completed, the material was placed in an Ar gas atmosphere at a temperature of 1500°C for 2 hours to reduce defects.
[0160] 2) Benzene hexathiophenol (6 g) and the commercially available CMK-3 ordered mesoporous carbon (2 g) treated as above were thoroughly mixed in a glove box, and then heated to 150°C for 10 h. Benzene hexathiophenol melted and diffused into the internal pores of CMK-3, and was physically confined to obtain C 6 S 6 H 6 @CMK-3.
[0161] 3) C obtained in step 2) 6 S 6 H 6 @CMK-3 and single lithium according to C 6 S 6 H 6 Mix well with lithium in a molar ratio of 1:5, heat to 200℃, and keep warm for 6h to obtain Li 5 HC6 S 6 @CMK-3.
[0162] Embodiment 15
[0163] This embodiment provides a lithium supplement material. The difference between this lithium supplement material and the lithium supplement material provided in embodiment 1 is that the porous conductive substrate has no pores, and the porous conductive substrate and the organic lithium salt are simply mixed.
[0164] The difference between the preparation method of the lithium supplement material and the preparation method provided in Example 1 is that in step 2), 2 g of asphalt is added to CMK-3 to be fully mixed with CMK-3. The decomposition product of asphalt can fill the pores of CMK-3, making the porous conductive substrate free of pores. In addition, step 3) is adjusted to simply mix the porous conductive substrate and the organic lithium salt without heating treatment.
[0165] Comparative Example 1
[0166] This comparative example provides a lithium supplement material Li 6 C 6 O 6 .
[0167] Comparative Example 2
[0168] This comparative example provides a lithium supplement material. The difference between the lithium supplement material and the positive electrode plate provided in Example 1 is that the lithium supplement material includes an inorganic lithium salt (Li 2 S) and a porous conductive substrate (CMK-3) are simply mixed.
[0169] The parameters of the lithium supplement materials provided by Examples 1 to 15 and Comparative Examples 1 to 2 are shown in Table 2:
[0170] Table 2 Parameters of lithium supplement materials provided in the examples and comparative examples
[0171]
[0172]
[0173] The lithium supplement materials provided in the above-mentioned Examples 1 to 15 and the lithium supplement materials provided in Comparative Examples 1 to 2 are respectively assembled into positive electrode sheets and lithium-ion batteries according to the following methods:
[0174] Positive electrode sheet: The lithium supplement material, SP and PVDF are mixed in a mass ratio of 90:4:6 to prepare a positive electrode slurry, the positive electrode slurry is coated on the surface of aluminum foil, vacuum dried at 110°C overnight, and rolled to obtain a positive electrode sheet;
[0175] Negative electrode: lithium sheet;
[0176] Electrolyte: Ethylene carbonate and ethyl methyl carbonate were mixed in a volume ratio of 3:7, and LiPF was added 6 , forming an electrolyte, LiPF 6 The concentration is 1 mol / L;
[0177] Diaphragm: Polypropylene microporous separator;
[0178] Lithium-ion battery assembly: Assemble button-type lithium-ion full batteries in an inert atmosphere glove box in the order of negative electrode sheet - separator - electrolyte - positive electrode sheet.
[0179] The electrochemical performance of each lithium-ion battery assembled in the above lithium-ion battery embodiment was tested under the following test conditions:
[0180] Electrochemical performance test:
[0181] The battery was charged at a rate of 0.1C with a cut-off voltage of 4.5V; the battery was charged at a constant voltage of 4.5V; after the charging process was completed, the battery was left to stand for 10 minutes and then discharged at a rate of 0.1C with a cut-off voltage of 2.5V; during the charging process, the charging platform was observed to obtain the decomposition voltage of the lithium supplement material; and the first cycle efficiency = (charge specific capacity / discharge specific capacity) * 100%. The calculation of the gram capacity is based on the total mass of the organic lithium salt and the porous conductive substrate.
[0182] Gas production test:
[0183] When the battery is charged and discharged for the first time, a battery gas production test device is used to detect the gas production of the battery after the first charge and discharge.
[0184] Water absorption test:
[0185] Weigh 0.5g of the material to be tested, place it in a constant temperature and humidity environment with a temperature of 25℃ and a humidity of 30%, spread it on a weighing paper, place it on a balance to weigh the mass, and record the mass of the material to be tested every t seconds (usually 20 seconds), recorded as m grams. The water absorption rate a = 2 (m-0.5) * 10 6 / t, unit is ppm / s.
[0186] The test results of the above lithium supplement materials and lithium batteries are shown in Table 3 below:
[0187] Table 3. Test results of embodiments and comparative examples
[0188]
[0189]
[0190] It can be seen from the test results of Examples 1 to 15 and Comparative Example 1 in Table 3 that the lithium replenishing material provided by the present invention has the characteristics of low delithiation platform point, low water absorption rate and low gas production compared with the ordinary organic lithium replenishing agent in the prior art; in addition, it can be seen from the test results of Examples 1 to 15 and Comparative Example 2 that the lithium replenishing material provided by the present invention has a higher first charge decomposition percentage than the ordinary lithium sulfide in the prior art, and the water absorption rate is much lower than that of the ordinary lithium sulfide, which also illustrates that the lithium replenishing material provided by the present invention has more superior performance than the existing ordinary lithium replenishing agent.
[0191] It can be seen from the test results of Example 1 and Example 2 in Table 3 that when the particle size of the organic lithium salt increases, the corresponding delithiation platform potential will also increase. Therefore, it is shown that the particle size of the organic lithium salt has a significant effect on the performance of the lithium supplement material, so the delithiation platform potential of the lithium supplement material can be adjusted by controlling the particle size of the organic lithium salt.
[0192] From the test results of Example 1, Example 3, Example 4 and Example 12 in Table 3, it can be seen that the mass ratio of the organic lithium salt and the porous conductive substrate will affect the lithium replenishment capacity of the lithium replenishment material and the electrical properties of the material. When the proportion of the organic lithium salt is small, the lithium replenishment capacity decreases significantly, and when the proportion of the porous conductive substrate is small, the delithiation platform potential will increase slightly.
[0193] From the test results of Example 1, Example 5, Example 6 and Example 15 in Table 3, it can be seen that the porosity of the porous conductive substrate will affect the performance of the lithium supplement material, mainly because if the porosity is too large, the passage inside the porous conductive substrate will be reduced, which is not conducive to electronic conduction; if the pores of the porous conductive substrate are too small, the difficulty of the lithium supplement material infiltrating into it will increase, the quality will decrease, and more organic lithium salts will stay on the outer surface of the porous conductive substrate, and the contact area with the porous conductive substrate will be relatively small. In addition, it can be seen from the test results of Example 7-Example 10 that the size of the pores in the porous conductive substrate has an impact on the performance of the lithium supplement material.
[0194] From the test results of Example 1, Example 11, Example 13 and Example 14 in Table 3, it can be seen that the solution provided by the present invention can also be applied to other types of organic lithium salts, such as pentacyclic Li 5 C 5 S 5 , chain-like Li 2 C 2 S 4 , Li containing hydrogen atoms 5 HC 6 S 6This also illustrates that the solution provided by the present invention is for all sulfur-containing organic lithium salts, regardless of whether the organic lithium salt is chain-shaped or cyclic, or whether the organic lithium salt contains hydrogen atoms.
[0195] In addition, it should be noted that the gas production and water absorption rate of the lithium supplement material provided by the present invention are closely related to the pore structure of the porous conductive substrate. Since the lithium removal products of Examples 1-15 and Comparative Example 2 do not contain gas, the gas generated in the test results is derived from the side reactions at the interface between the organic lithium salt and the porous conductive substrate and the electrolyte, most of which is CO 2 , CO and other gases, and the larger the porosity and specific surface area of the porous conductive substrate, the more side reactions may occur, and the amount of gas produced will increase accordingly; at the same time, the water absorption rate also has a similar rule, so it can be seen that in Example 12 and Example 15, the water absorption rate and gas production are the lowest due to the absence of a porous conductive substrate, and the main gas production comes from the interface side reaction between the organic lithium salt and the electrolyte. For Comparative Example 1, its gas production is the highest (5.8ppm / s), mainly because Li 6 C 6 O 6 The delithiation product C 6 O 6 After dissolving in the electrolyte, the interface side reaction between the electrolyte and the porous conductive substrate is intensified. 6 C 6 S 6 Has certain advantages.
[0196] In addition, the present invention also provides positive electrode sheets of Examples 16 to 18 and Comparative Example 3. The lithium supplement materials in Examples 16 to 18 and Comparative Example 3 all use the lithium supplement materials provided in Example 1 above.
[0197] Example 16
[0198] This embodiment provides a positive electrode plate. The positive electrode plate includes a current collector (aluminum foil) and a positive electrode material layer, and the positive electrode material layer includes a positive electrode active material (LiFePO 4 ), lithium supplement materials (Li 6 C 6 S 6 @CMK-3), conductive agent (SP) and binder (PVDF).
[0199] The positive electrode material layer includes a first layer, a second layer and a third layer of the same thickness, and the total thickness of the positive electrode material layer is 150 μm. The first layer includes 78.8% of positive electrode active material, 16.2% of lithium supplement material and 5% of conductive agent / binder by mass fraction; the second layer includes 93.2% of positive electrode active material, 1.8% of lithium supplement material and 5% of conductive agent / binder by mass fraction; the third layer includes 95% of positive electrode active material and 5% of conductive agent / binder by mass fraction.
[0200] The method for preparing the positive electrode sheet comprises the following steps:
[0201] 1) The positive electrode active material, lithium supplement material, conductive agent and binder are dispersed and stirred together with NMP (N-methylpyrrolidone) according to the above-mentioned stoichiometric ratio to form a slurry, and then coated and dried on aluminum foil to obtain the first layer.
[0202] 2) The positive electrode active material, lithium supplement material, conductive agent and binder are dispersed and stirred together with NMP (N-methylpyrrolidone) according to the above-mentioned stoichiometric ratio to form a slurry, and then coated on aluminum foil and dried to obtain the second layer.
[0203] 3) The positive electrode active material, the conductive agent and the binder are dispersed and stirred together with NMP (N-methylpyrrolidone) according to the above-mentioned stoichiometric ratio to form a slurry, and then coated on an aluminum foil and dried to obtain the third layer.
[0204] Embodiment 17
[0205] This embodiment provides a positive electrode plate. The difference between this positive electrode plate and the positive electrode plate provided in embodiment 16 is that the positive electrode material layer includes a first layer and a second layer of the same thickness.
[0206] The difference between the preparation method of the positive electrode plate and the preparation method provided in Example 16 is that step 3) is not performed.
[0207] Embodiment 18
[0208] This embodiment provides a positive electrode plate. The difference between this positive electrode plate and the positive electrode plate provided in Example 16 is that: the first layer includes 81.4% of positive electrode active material, 13.6% of lithium supplement material and 5% of conductive agent / binder by mass fraction; the second layer includes 90.6% of positive electrode active material, 4.4% of lithium supplement material and 5% of conductive agent / binder by mass fraction.
[0209] The preparation method of the positive electrode plate is the same as the preparation method provided in Example 16.
[0210] Comparative Example 3
[0211] This comparative example provides a positive electrode plate. The difference between this positive electrode plate and the positive electrode plate provided in Example 16 is that the lithium supplement material is evenly distributed in the positive electrode material layer.
[0212] The difference between the preparation method of the positive electrode plate and the preparation method provided in Example 16 is that: 1) the positive electrode active material, lithium supplement material, conductive agent and binder are dispersed and stirred together with NMP (N-methylpyrrolidone) to form a slurry, and then coated and dried on aluminum foil to obtain a positive electrode material layer.
[0213] The positive electrode plate parameters provided by Example 16 to Example 18 and Comparative Example 3 are shown in Table 4:
[0214] Table 4 Parameters of positive electrode sheets provided in the examples and comparative examples
[0215]
[0216] The positive electrode sheets provided in the above-mentioned Examples 16 to 18 and the positive electrode sheets provided in Comparative Example 3 were respectively assembled into lithium-ion batteries according to the above-mentioned method, and the electrochemical performance of the lithium-ion batteries was tested. The test results are shown in Table 5 below:
[0217] Table 5. Test results of Examples 16-18 and Comparative Example 3
[0218]
[0219] From the test results of Examples 16 to 18 and Comparative Example 3 in Table 5, it can be seen that the present invention can improve the lithium replenishment capacity of the battery at 0.1C and 0.3C charging rates by redesigning the distribution of the lithium replenishment material in the positive electrode plate, and reduce the lithium de-lithiation platform of the lithium replenishment material, and the capacity retention rate of 0.3C relative to 0.1C is greatly improved. In addition, it should be noted that when the charging rate is increased from 0.1C to 0.3C, the gram capacity of the lithium replenishment material decreases to a certain extent, and the lithium de-lithiation platform potential of the lithium replenishment material increases to a certain extent, which is caused by polarization and has nothing to do with the design of the lithium replenishment material itself and the positive electrode plate.
[0220] It can be seen from the test results of Example 16 and Example 17 in Table 5 that since there is no third layer in the positive electrode plate, the thickness of the plate changes from 150 μm to 100 μm. The reduction in thickness is conducive to electrolyte infiltration and ion diffusion, so its polarization degree is smaller, the lithium desorption platform at a rate of 0.3C is lower, and the capacity retention rate is higher.
[0221] It can be seen from the test results of Example 16 and Example 18 in Table 5 that by setting the distribution of the lithium-supplementing material in a gradient on the positive electrode sheet, the mass fraction of the lithium-supplementing material close to the current collector is higher, and this part of the lithium-supplementing material will gradually dissolve in the electrolyte during the delithiation process, so more pores are gradually generated in the positive electrode sheet, which in turn promotes the full infiltration of the electrolyte close to the current collector side, which is beneficial to promote the transmission of ions during the electrochemical reaction, thereby reducing the degree of polarization to a certain extent and improving the rate performance of the electrode.
[0222] In the description of the embodiments of the present invention, it should be noted that the orientation or positional relationship of terms such as "center", "up", "down", "left", "right", "vertical", "horizontal", "inside" and "outside" are based on the orientation or positional relationship described in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention.
[0223] What is disclosed above is only a preferred embodiment of the present invention, and it certainly cannot be used to limit the scope of rights of the present invention. Ordinary technicians in this field can understand that all or part of the processes of the above embodiment and equivalent changes made according to the claims of the present invention still fall within the scope covered by the present invention.
Claims
1. A lithium supplement material, characterized in that: The lithium supplement material includes an organic lithium salt, and the chemical formula of the organic lithium salt includes Li x1 H x2 C y S z , where 6>x1>0, 5≥x2≥0, y≥1, z≥1.
2. The lithium supplement material according to claim 1, characterized in that: The organic lithium salt comprises a cyclic organic lithium salt, wherein y≥3, z=y, and the delithiation product of the cyclic organic lithium salt is C y S z , the C y S z Dissolved in electrolyte.
3. The lithium supplement material according to claim 1, characterized in that: The lithium supplement material further includes a porous conductive substrate, and the organic lithium salt is combined on the porous conductive substrate.
4. The lithium supplement material according to claim 3, characterized in that: The porous conductive substrate is a porous structure having holes and / or pores, and at least a portion of the organic lithium salt is confined and grown in the holes or pores.
5. The lithium supplement material according to claim 4, characterized in that: The particle size of the organic lithium salt is 3nm to 100nm, and / or The mass fraction of the organic lithium salt in the lithium supplement material is 60% to 90%, and / or The organic lithium salt has a water absorption rate of less than 3 ppm / s in an environment with a temperature of 25° C. and a humidity of 30% and / or The porosity of the porous conductive substrate is 50% to 95%, and / or The pore size of the porous conductive substrate is 5nm to 250nm, and / or The porous conductive substrate comprises mesopores and macropores, wherein the volume proportion of the mesopores is 20% to 50%, and the volume proportion of the macropores is 50% to 70%; and / or The electronic conductivity of the porous conductive substrate is 1×10 3 S / m~1×10 7 S / m; and / or The porous conductive substrate includes one or more of ordered mesoporous carbon, Ketjen black, carbon black, disordered porous carbon, porous graphene, carbon nanotubes, and carbon fibers.
6. A method for preparing a lithium supplement material, characterized in that: include: combining carbon-sulfur organic matter and a lithium source to obtain a precursor material; The precursor material is subjected to electrochemical treatment or thermal treatment to react the carbon-sulfur organic matter with the lithium source to obtain an organic lithium salt; The chemical formula of the organic lithium salt includes Li x1 H x2 C y S z , where 6>x1>0, 5≥x2≥0, y≥1, z≥1.
7. A positive electrode material, characterized in that: The positive electrode material comprises an active material and the lithium supplement material according to any one of claims 1 to 5, or comprises a lithium supplement material obtained by the preparation method of the lithium supplement material according to claim 6.
8. A secondary battery, characterized in that: The invention comprises a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises the positive electrode material as claimed in claim 7.
9. The secondary battery according to claim 8, characterized in that: The positive electrode includes a positive electrode plate, which includes a current collector and a positive electrode material layer arranged on the current collector, the positive electrode material layer includes the positive electrode material, and the lithium-replenishing material content on the side of the positive electrode material layer close to the current collector is greater than the lithium-replenishing material content on the side of the positive electrode material layer away from the current collector.
10. The secondary battery according to claim 9, characterized in that: The positive electrode material layer includes a first layer and a second layer connected along the thickness direction, wherein the first layer is connected to the current collector, the mass fraction of the lithium-replenishing material in the first layer is 60% to 90% of the lithium-replenishing material in the positive electrode material layer, and the mass fraction of the lithium-replenishing material in the second layer is 10% to 40% of the lithium-replenishing material in the positive electrode material layer.